2016
DOI: 10.5935/0103-5053.20160074
|View full text |Cite
|
Sign up to set email alerts
|

On-line Green Solid Phase Extraction of Trace Rare Earth Elements and Uranium in Environmental Samples and ICP OES Detection

Abstract: An on-line solid phase extraction (SPE) method using mini column packed with natural sorbent based on cotton roll dyed by quinalizarin was developed for simultaneously pre-concentration of rare earth elements and uranium at trace levels in environmental samples followed by inductively coupled plasma optical emission spectrometry (ICP OES) determination. Various parameters such as sample and eluent flow rate, sample volume and matrix ions on the method efficiency have been investigated. Under the optimized cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46 Additionally, for the first time, the proposed sensor can be applied in portable analyzer, which enables us to perform field analysis of U(VI) in concentrations that actually occur in environmental water samples. Furthermore, the obtained limit of detection is significantly lower than obtained for another techniques applied for uranium determination in environmental samples: 2.4 nmol L −1 and 1.8 nmol L −1 for ICP-OES, 12,13 210 nmol L −1 for ICP-MS, 14 2.5 nmol L −1 for spectrophotometry 17 and 0.13 nmol L −1 for fluorometric determination of uranium. 19 In addition, the precision of the proposed DPAdSV technique using the SPCE/PbF as an intra-day and inter-day precision was tested by recording ten voltammograms at the concentration of U(VI) of 0.5 nmol L −1 .…”
Section: Optimization Of Lead Film Plating and U(vi) Determinationmentioning
confidence: 66%
See 1 more Smart Citation
“…[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]46 Additionally, for the first time, the proposed sensor can be applied in portable analyzer, which enables us to perform field analysis of U(VI) in concentrations that actually occur in environmental water samples. Furthermore, the obtained limit of detection is significantly lower than obtained for another techniques applied for uranium determination in environmental samples: 2.4 nmol L −1 and 1.8 nmol L −1 for ICP-OES, 12,13 210 nmol L −1 for ICP-MS, 14 2.5 nmol L −1 for spectrophotometry 17 and 0.13 nmol L −1 for fluorometric determination of uranium. 19 In addition, the precision of the proposed DPAdSV technique using the SPCE/PbF as an intra-day and inter-day precision was tested by recording ten voltammograms at the concentration of U(VI) of 0.5 nmol L −1 .…”
Section: Optimization Of Lead Film Plating and U(vi) Determinationmentioning
confidence: 66%
“…Different instrumental techniques enable uranium determination in environmental samples. Suitable techniques for this purpose are, for example inductively coupled plasma optical emission spectrometry (ICP-OES), 12,13 inductively coupled plasma optical emission spectrometry (ICP-MS), [14][15][16] spectrophotometry, 17,18 fluorometry, 19 gamma-ray spectroscopy 20 or accelerator mass spectrometry. 21 However, each of them has limitations which hamper their use, e.g.…”
mentioning
confidence: 99%
“…It has been reported that biodegradable aminophenol-functionalized resin can be used for green determination and preconcentration of metal ions including copper (Cu), zinc (Zn), lead (Pb) and cadmium (Cd) in drinking tap water [23]. Solid phase extraction and preconcentration method using a natural sorbent based on cotton roll dyed by quinalizarin has also been successfully applied for determination of 14 rare earth elements as well as uranium with acceptable accuracy, precision and significant enrichment factor [24]. Other environmental friendly method has also been successfully used for preconcentration and simultaneous determination of cobalt (Co) and lead (Pb) in waste water sample using 8-hydroxyquinoline (oxine) as a chelating agent [25].…”
Section: Discussionmentioning
confidence: 99%
“…Beside these methods, the widespread variety of solid materials suitable for solid phase extraction-preconcentration of uranium ions results in a large body of investigations concerning the application of this technique for determination of trace amounts of uranium ions in water samples. [11][12][13][14][15] Ordered mesoporous materials are among recently developed effective adsorbents with high surface areas, uniform pore structures, adequate mechanical stabilities and high adsorption capacities. 16 SBA-15 based adsorbents are a group of common mesoporous molecular sieves.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Thus, a variety of preconcentration procedures, including dispersive liquid-liquid extraction, 7 cloud point extraction, 8 electromembrane extraction 9 and co-precipitation, 10 have been investigated. Beside these methods, the widespread variety of solid materials suitable for solid phase extraction-preconcentration of uranium ions results in a large body of investigations concerning the application of this technique for determination of trace amounts of uranium ions in water samples.…”
Section: Introductionmentioning
confidence: 99%